Workshop of revolution : plebeian Buenos Aires and the Atlantic world, 1776-1810 - Johnson, Lyman L. (Online access with subscription: Duke University Press., 2011)
Workshop of Revolution is a historical account of the economic and political forces that propelled the artisans, free laborers, and slaves of Buenos Aires into Argentina s struggle for independence.